Ответы и объяснения

2014-04-10T00:18:20+04:00
1)=30*(х^4-7)^29 * 4x^3=120x^3 *(x^4-7)^29
2)=3* (3x^2-5) / 4* на корень четвертой степени из выражения x^3-5x+5
3)=40x^19+30x^9+10x^4+4x^3
4)=2x*(x-3)+x^2+9=3x^2-6x+9
5)=2x*(x+4)-(x^2-3) / (x+4)^2=x^2+8x+3 / (x+4)^2
6)=x^3-x^2+x-1
7)=2x*(x^3-3x+2)+(3x^2-2)(x^2+5)=5x^4+7x^2+4x-10
8)=-9/x^4  -  1/(5* на корень пятой степени из x^4)  -  5/(3*∛x^4)
9)=(3x^2-3)(1-2x)+2(x^3-3x)/ (1-2x)^2=(-4x^3+3x^2-3)/(1-2x)^2
10)=5*(3-2x^3)^4 * (-6x^2)=-30x^2 * (3-2x^3)^4